Expressive Illocutionary Acts in a Political Talk Show - Rašová, Dominika (Poznańskie Studia Slawistyczne, 2015)
This article focuses on the pragmatic dimension of language phenomena with respect to the expressive and emotional aspect of Slovak and German. The aim is to monitor the use of language and the relationship to language users and relationship to language sign. The study focuses on the intentions of users and the importance of pragmatic language of political and publicistic discourse. The primary focus will be on expressive illocutionary acts and their specific realisation.